Microstructure Evolution of Gas-Atomized β-Solidifying γ-TiAl Alloy Powder during Subsequent Heat Treatment - Sung-Hyun Park; Ozkan Gokcekaya; Ryosuke Ozasa; Ken Cho; Hiroyuki Y. Yasuda; Myung-Hoon Oh; Takayoshi Nakano (Crystals, 2023)
To promote the use of γ-TiAl alloys in various domains, such as the aerospace industry, it is pivotal to investigate the unusual phase transformation from rapidly solidified and metastable γ-TiAl toward the equilibrium state. In this study, the microstructure characteristics of gas-atomized β-solidifying Ti-44Al-6Nb-1.2Cr alloy powder, in terms of the effect of rapid solidification on microstructure evolution, were explored in comparison with cast materials. The phase constitution, morphology, and crystallographic orientation between phases were noted to be distinct. Furthermore, subsequent heat treatment was conducted at different temperatures using gas-atomized powder. The transition from the metastable to equilibrium state was observed, wherein firstly, the γ phase precipitated from the retained α2 phase, forming an α2/γ lamellar microstructure. In intensified heat-treatment conditions adequate for cellular reaction, β/γ cells were formed at the grain boundaries of α2/γ lamellar colonies. The findings highlight the overall phase transformation during rapid solidification and continuous microstructural evolution from the nonequilibrium to the equilibrium state. This research can bridge the gap in understanding the effect of the solidification rate on microstructural evolution and contribute to enhanced comprehension of the microstructure in other domains involving rapid solidification, such as the additive manufacturing of γ-TiAl alloys.